CUTANEOUS MANIFESTATIONS IN DIABETES MELLITUS:A SYSTEMATIC REVIEW OF PREVALENCE AND CLINICAL CORRELATES (Bangladesh Journal of Medical Science, 2026)
Objective This review was undertaken to determine the frequency and clinical correlates of cutaneous lesions in individuals with diabetes mellitus (DM). Materials and methods PRISMA guidelines were followed for this review. From January 2016 to July 2025, PubMed, Scopus, Web of Science, and Google Scholar were searched using relevant keywords and medical subject headings. A thorough analysis of the references from the selected research was performed to identify literature that was not included in digital repositories. After an impartial search, two reviewers assessed the records using the evaluation criteria. The selected observational studies were evaluated using a cross-sectional critical evaluation tool developed from the Newcastle-Ottawa quality assessment scale for cohort studies. Results Following a rigorous search, 70 duplicates were deleted from 252 records before screening. Title and abstract screening eliminated 118 redundant studies from the remaining 182 records. Seven of 64 requested full-text papers were unavailable, leaving 57 for eligibility evaluation and 25 cross-sectional studies for the review. Fungal, bacterial, pruritus, xerosis, diabetic dermopathy, and ulcers were common cutaneous symptoms. Necrobiosis lipoidica, alopecia areata, scleredemadiabeticorum, and granuloma annulare were rare. Except for two poor-quality studies and two goodquality studies, the remaining studies were of fair quality. Conclusion This investigation delineates the importance of early identification and understanding of the aetiology of cutaneous manifestations in DM. These approaches can prevent complications, reduce impairment, and enhance quality of life in afflicted individuals by enabling rapid intervention, enhancing glycaemic control, and addressing modifiable risk factors such as obesity and poor disease management.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S199-S210